TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP BELAJAR IPA DI KELAS V SD - Desy Eka Muliani; Zaturrahmi; Oni Putri Lestari; Nadia Deswita (Jurnal Riset Pendidikan Dasar Dan Karakter, 2021)
Background of the problem in this research is during the learning process, the learning process is still teacher centered (teacher centered learning), so that the students have not been involved and lees focus. The division of the group that carried out theteacher’s not in a heterogeneous, so that the impact on students. Students are less motivated for the award of the teacher. This study aims to determine the effect of cooperative learning model type student teams achievement division (STAD) towards science learning outcomes of students of class V elementary school 33 Kalumbuk PadangThis research type that is research quantitative, with desain research is quasi-experimental design. Design with Nonequivalent Control Group Design, in this design there are two classes, then used as the experimental class and the control class. The results of this study, shows that 2.594 greater than = 1.691. Based on the results, this study has proven that the use of cooperative learning model type student teams achievement division (STAD) influences significantly on student’s learning outcomes in natural science learning materials on digestive organs in the class V SD Negeri 33 Kalumbuk Padang academic year 2017/2018.